Cyber Warfare as a Use of Force against Third-Party Countries: The Perspective of International Law - Tareq Hamid Al-Fahdawi (Groningen Journal of International Law, 2024)
The use of force in international relations takes different forms and changes year by year due to the development of cyber technology. The problem mentioned in this study is that the Charter of the United Nations (UN Charter) and international law have not considered weapons development and future weapons that may be used in international relations, as Russia has used such weapons during the war against Ukraine. Unfortunately, cyber technologies were used to deter and weaken Ukraine’s chance to gain an advanced result on the ground. Although such cyber operations can cause the same physical damage as other weapons, the international community is still struggling to determine whether using a cyber weapon is considered a use of force. This study argues that cyber attacks against third-party countries that support Ukraine during the war may count as the use of force and a breach of Article 2(4) of the UN Charter.